A versatile 3D-printable hydrogel for antichondrosarcoma, antibacterial, and tissue repair. (10th February 2023) - Zhu, Wenxiang; Zhou, Zheng; Huang, Yuting; Liu, Hairong; He, Ning; Zhu, Xiaolong; Han, Xiaoxiao; Zhou, Dengming; Duan, Xuanchu; Chen, Xin; He, Yahui; Meng, Xiaolin; et al.
Highlights: A novel hydrogel with biological activity and photothermal effect was synthesized. The hydrogel can exert anti-tumor and antibacterial effect through photothermal effect. The hydrogel can effectively promote the repair of articular cartilage defects in vivo . Abstract: Following operative treatment of chondrosarcoma, post-surgery tissue reconstruction may be confronted with daunting challenges, including the delayed self-repair of defective tissue, tumor recurrence, and bacterial infection. To overcome these challenges, a methacrylic anhydride (MA) modified sericin (SerMA) solution mixed with procyanidins (PC) loaded polydopamine (PDA) modified ZIF-8 (PC@ZIF-8@PDA) nanoparticles to form a multifunctional PC@ZIF-8@PDA/SerMA hydrogel after exposure under blue light. Hydrogel products with pre-designed shapes were printed out by using the SerMA solution carrying PC@ZIF-8@PDA nanoparticles and chondrocytes, indicating that PC@ZIF-8@PDA/SerMA hydrogels with personalized shapes can be fabricated via 3D printing. Photocrosslinked PC@ZIF-8@PDA/SerMA hydrogel is able to kill chondrosarcoma cells and bacteria, like Staphylococcus aureus (S. aureus), and Escherichia coli (E. coli), by its photothermal activity combined with near-infrared radiation (NIR). The PC@ZIF-8@PDA/SerMA hydrogel exhibited an antioxidative activity and a good biocompatibility and was easily monitored by its florescent and photoacoustic properties. Rabbit articular cartilage defects were efficiently repaired by PC@ZIF-8@PDA/SerMA hydrogels with encapsulated corresponding autologous chondrocytes, and mice skin burning wounds were swiftly regenerated by applying this hydrogel. Hence, the PC@ZIF-8@PDA/SerMA hydrogel can be potentially applied to the clinic treatment of chondrosarcoma and tissue defect repair after chondrosarcoma resection due to its multifunction in the future. Graphical abstract: Image, graphical abstract